PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA KANTOR PELAYANAN GRAPARI TELKOMSEL CABANG BATAM - Ardika Triwibowo; Ramon Zamora (EQUILIBIRIA, 2016)
This study aims to determine the Effect of Work Environment, Work Discipline, And Organizational Commitment on employee performance at Telkomsel Customer Service office Batam. Sampling technique used in this study is a probability sampling, by using the method of proportionate stratified random sampling, the total sample determined by the Slovin formula, with the total employee population is 112 employees, which taken as sample is 53 respondents. Types of data sources used are primary data, obtained from the respondents' answers on the questionnaire, and secondary data obtained from the data or documents of PT. Telkomsel, as well as reference books and journals from previous research. Techniques of data retrieval that is by distributing questionnaires to 53 respondents , and documentation from the company is a brief history , organizational structure , employee data , and others. Data analysis method used is multiple linear regression analysis using SPSS 20 for Windows. The study states that ( 1 ) partially Work Environment have positive and significant effect on the employee performance, ( 2 ) Work Discipline have positive and not significant effect on the employee performance, ( 3 ) Organizational Commitment have positive and significant effect on the employee performance ( 4 ) Effect of Work Environment, Work Discipline and Organizational Commitment have positive and significant effect simultaneously on the employees performance at Telkomsel Customer Service office Batam. With the value of adjusted R square of 0.543, in this case shows that the performance of employees affected by variables Training, Organizational Culture and Leadership Style is 54.3%. The remaining 45.7% is influenced by other variables which is not included in this research. With multiple linear regression equation Y = 2,518+ 0,271X1 + 0,239X2 +0,393X3 + e